Robust circadian rhythms in organoid cultures from PERIOD2::LUCIFERASE mouse small intestine - Sean R. Moore; Jill Pruszka; Jefferson Vallance; Eitaro Aihara; Toru Matsuura; Marshall H. Montrose; Noah F. Shroyer; Christian I. Hong (The Company of Biologists, 2014)
Disruption of circadian rhythms is a risk factor for several human gastrointestinal (GI) diseases, ranging from diarrhea to ulcers to cancer. Four-dimensional tissue culture models that faithfully mimic the circadian clock of the GI epithelium would provide an invaluable tool to understand circadian regulation of GI health and disease. We hypothesized that rhythmicity of a key circadian component, PERIOD2 (PER2), would diminish along a continuum from ex vivo intestinal organoids (epithelial 'miniguts'), nontransformed mouse small intestinal epithelial (MSIE) cells and transformed human colorectal adenocarcinoma (Caco-2) cells. Here, we show that bioluminescent jejunal explants from PERIOD2::LUCIFERASE (PER2::LUC) mice displayed robust circadian rhythms for >72 hours post-excision. Circadian rhythms in primary or passaged PER2::LUC jejunal organoids were similarly robust; they also synchronized upon serum shock and persisted beyond 2 weeks in culture. Remarkably, unshocked organoids autonomously synchronized rhythms within 12 hours of recording. The onset of this autonomous synchronization was slowed by >2 hours in the presence of the glucocorticoid receptor antagonist RU486 (20 μM). Doubling standard concentrations of the organoid growth factors EGF, Noggin and R-spondin enhanced PER2 oscillations, whereas subtraction of these factors individually at 24 hours following serum shock produced no detectable effects on PER2 oscillations. Growth factor pulses induced modest phase delays in unshocked, but not serum-shocked, organoids. Circadian oscillations of PER2::LUC bioluminescence aligned with Per2 mRNA expression upon analysis using quantitative PCR. Concordant findings of robust circadian rhythms in bioluminescent jejunal explants and organoids provide further evidence for a peripheral clock that is intrinsic to the intestinal epithelium. The rhythmic and organotypic features of organoids should offer unprecedented advantages as a resource for elucidating the role of circadian rhythms in GI stem cell dynamics, epithelial homeostasis and disease.